Production of Elements for an Innovative Energy-Saving Prefabricated Construction under the Project Plus Energy Prefab House - Jasiczak, Jozef; Gerard, Rene-Xavier; Wojtasik, Lech; Przychocki, Blazej; Bednarek, Jakub; Cichocki, Krzysztof; Kołodziej, Jarosław (IOP conference series. Materials Science and Engineering, 2019)
In 2012, the annual International Competition Future Project Awards of the prestigious English, Architectural Review magazine, architect Lech Wojtasik from the Architectural Studio in Pila was awarded first place in the Sustainability Prize category, for the Plus Energy Prefab House project. It is a housing construction system, implemented by a factory technology of precast concrete construction, based on the use of renewable energy sources, energy efficiency, ecology and economics. The project refers to the energy and climate package for 2020-2030, first proposed by the leaders of EU countries in 2009 and later by the European Commission in 2014. Winning this international award resulted in the reconstruction of the existing architectural complex with construction designers, prefabrication technologists and engineers from the fields of effective thermal management and air exchange in the building. They developed a concept of a detached single-family house with a steep roof and passive properties. In 2016, the team received a grant from the National Centre for Research and Development (NCRD) for the implementation of a prototype building and the development of a precast production technology. The project implemented as part of an NCRD task of a prototype single-family home and adopted architectural and structural solutions with modern heating and air-conditioning systems are the subject of the presented article.